115 Two Cases of "Drained and Retained" Inflatable Penile Prosthesis and Artificial Urinary Sphincter Reservoirs causing Small Bowel Obstruction. Issue 1 (1st April 2022) - Loloi, J; Davila, J; Matloubieh, J; Gottlieb, J; Maria, P; Donnelly, J; Small, A
ABSTRACT: Introduction: Inflatable penile prosthesis (IPP) and artificial urinary sphincter (AUS) are the most common surgical implants in the field of men's health. Infected or defective implants can be removed or replaced. The "drain and retain" strategy has been described as generally safe when prosthetic reservoirs are not easily retrieved. However, case reports of complications related to retained balloons have been described including erosion into the bowel and bladder, intraperitoneal migration and vascular compression. Here we describe two rare cases of reservoir-induced small bowel obstruction (SBO) from IPP and AUS reservoirs. Objective: Describe two rare cases of retained IPP and AUS reservoirs causing SBO. Methods: Single institutional retrospective case series. Results: Case 1: 75 year old male who underwent IPP placement in 2001. Due to device malfunction, IPP cylinders were removed and replaced with 2-piece device in 2017, and the reservoir was "drained and retained." The patient presented 4 years later with abdominal pain, nausea/vomiting, and right lower quadrant (RLQ) feculent cutaneous drainage. CT scan showed SBO with a transition within the terminal ileum due and an endoluminal foreign body in the cecum (consistent with the retained reservoir) (Figure 1A). Additionally, a contained bowel perforation with entero-cutaneous fistula tract to the skin was identified. Diagnostic laparoscopy revealed a thickened terminal ileum, walled-off perforation in the RLQ (Figure 1B) thought to be due to reservoir entry into the bowel, and a fistula to the right abdominal wall. The bowel was resected, thorough investigation including right-sided colonoscopy was unable to identify the reservoir, and primary anastomosis was performed. Follow up CT scan 3 days later showed passage of reservoir, presumably in the patient's bowel movements. Case 2: 81 year old male with a history of AUS placement in 2016. The device was removed for infection 5 years later. The reservoir was "drained and retained" given difficult access and no sign of reservoir infection. One month later, he presented with abdominal distention, nausea and vomiting. A CT scan revealed dilated loops of small bowel with an abrupt transition point in the RLQ adjacent to the retained reservoir (Figure 1C). Exploratory laparotomy showed SBO with the reservoir and tubing embedded into the small bowel wall (Figure 1D). The foreign bodies were successfully retrieved and the affected bowel was resected and repaired with a primary anastomosis. Conclusions: These two cases of SBO due to IPP and AUS reservoirs show a potential danger of the "drain and retain" strategy, especially when reservoirs are placed intraperitoneal. These cases may be helpful to inform patient counseling on the rare risks of implant revision surgery. Innovative means of reservoir retrieval at explantation are needed to mitigate these risks. Disclosure: No